Battle Of The Robots - Undergraduates test their technological skills - The Star, Sarah Chew (2008)
Cameras are in place, lights are falshing and students cheer and clap with their plastic sticks. In the middle of the hall teams of tertiary students are busy positioning their robots on the game court, which has pots of 'cheese balls' around it and three yellow blocks of butter on raised bowls in the centre.